A strategy for large-scale scalar advection in large eddy simulations that use the linear eddy sub-grid mixing model. Issue 10 (1st October 2018) - Arshad, Salman; Kong, Bo; Kerstein, Alan; Oevermann, Michael
Abstract : Purpose: The purpose of this numerical work is to present and test a new approach for large-scale scalar advection (splicing) in large eddy simulations (LES) that use the linear eddy sub-grid mixing model (LEM) called the LES-LEM. Design/methodology/approach: The new splicing strategy is based on an ordered flux of spliced LEM segments. The principle is that low-flux segments have less momentum than high-flux segments and, therefore, are displaced less than high-flux segments. This strategy affects the order of both inflowing and outflowing LEM segments of an LES cell. The new splicing approach is implemented in a pressure-based fluid solver and tested by simulation of passive scalar transport in a co-flowing turbulent rectangular jet, instead of combustion simulation, to perform an isolated investigation of splicing. Comparison of the new splicing with a previous splicing approach is also done. Findings: The simulation results show that the velocity statistics and passive scalar mixing are correctly predicted using the new splicing approach for the LES-LEM. It is argued that modeling of large-scale advection in the LES-LEM via splicing is reasonable, and the new splicing approach potentially captures the physics better than the old approach. The standard LES sub-grid mixing models do not represent turbulent mixing in a proper way because they do not adequately represent molecular diffusion processes and counter gradient effects. Scalar mixing in turbulent flow consists of two different processes, i.e. turbulent mixing that increases the interface between unmixed species and molecular diffusion. It is crucial to model these two processes individually at their respective time scales. The LEM explicitly includes both of these processes and has been used successfully as a sub-grid scalar mixing model (McMurtry et al ., 1992 ;Sone and Menon, 2003 ). Here, the turbulent mixing capabilities of the LES-LEM with a modified splicing treatment are examined. Originality/value: The splicing strategy proposed for the LES-LEM is original and has not been investigated before. Also, it is the first LES-LEM implementation using unstructured grids.